INVESTIGATION OF QUASI SOLID ELECTROLYTE DYE SENSITIZED SOLAR CELLS (DSSC) PERFORMANCE USING SYNGONIUM PODOPHYLLUM SCHOTT AS NATURAL DYE AND COUNTER ELECTRODE - GHUFIRA OKTARIZA, LINGGA
The global energy crisis is increasingly critical from time to time, encouraging the development of alternative energy on earth. The radiance of sunlight to the earth when converted into electrical energy can be used as a promising alternative energy in the future. Silicon solar cells as devices that convert sunlight into electrical energy, have been distributing commenercially for a long time with an efficiency of 10-20%. The difficult fabrication process and high cost requirement become a challenge in the its distribution. In addition, silicone material may cause unfriendly effects to environment after its use. So dye synthesized solar cells, better known as DSSC (Dye Sensitized solar cells), which is easier and cheaper in its production is developed. The extraction of chlorophyll from the Syngonium Pophyllum Schott leaves is used as an alternative photosensitizer of the rhutenium dye which is proven to be toxic in the environment. The extraction of chlorophyll leaf using ethanol solvent resulted in the peak absorbance of chlorophyll at visible light wavelength range, 445-455 nm and 666 nm. The Tauc equation analysis of absorbance data yields the smallest gap energy of chlorophyll in sample 5 i.e., ~1.91 eV. In electrochemical analysis, there are the peak of oxidation and reduction in chlorophyll. From these peaks, the HOMO and LUMO energy levels correlated with the chlorophyll gap energy is obtained by using the Bredas equation. Sample 5 has the lowest HOMO energy of ~4.227 eV with ~2.362 eV LUMO energy. The counter electrode component plays a very important role in collecting electrons from the external circuit. Platinum (Pt) is a counter electrode that is used so far. Since this material is available in limited quantities, so that needs high cost in fabricating DSSC devices. Pedot:PSS as conductive polymer and carbonized dye chlorophyll material are used as an alternative to Pt counter electrode. The carbonized chlorophyll dye is synthesized from chlorophyll by activating chemically and followed by carbonization process at 850 Ã‚Â° C under argon gas flow for 2 hours. Based on Cyclic Voltametry characterization, Pt is still better than Pedot: PSS and carbonized chlorophyll dye, with faster electron transfer rate resulting ?Ep: 0,136 V. The conversion efficiency of DSSC devices using the same natural dye of chlorophyll (sample 5) yields the highest value of 1.526% with 1.2 V Voc, with platinum counter electrode and quasi solid electrolyte of Poly Ethylene Oxide (PEO). PEO as quasi solid electrolyte performance is much better than HSE electrolyte with conversion efficiency of 0.999% on platinum counter electrode. The Pedot : PSS and carbonized chlorophyll dye counter electrodes resulted in lower conversion efficiency of 0.377% and 0.308% with HSE electrolyte, and 0.435% and 0.239% with PEO quasi solid electrolyte. Although the performance of the Pedot:PSS and carbonized chlorophyll dye counter electrodes is not as good as platinum, but the two materials can be an alternative counter electrode because of abundant materials, non toxic and low cost.